Climate variability and sea level change during the Holocene: Insights from an inorganic multi-proxy approach in the SE Brazilian continental shelf. (1st March 2019) - Lazzari, Letícia; Wagener, Angela L.R.; Carreira, Renato S.; Godoy, José Marcus O.; Carrasco, Gonzalo; Lott, Carolina T.; Mauad, Cristiane R.; Eglinton, Timothy I.; McIntyre, Cameron; Nascimento, Gabriela S.; Boyle, Edward A.
Abstract: Two sediment cores collected in the shelf off Rio de Janeiro (RJ13-01B: 10.8 cal kyr BP, and RJ13-02B: 4.7 cal kyr BP) were investigated in high-resolution to evaluate changes in sedimentary processes and paleoclimatic and paleoceanographic variability during the Holocene in the Southeastern Brazil. Information from inorganic proxies of continental input (Al/Ca and Fe/Ca), redox-sensitive elements (Fe/Al, V/Al and Mn/Al), paleoproductivity (Sr/Al, Cd/Al and Ba/Al), as well as data for grain size, geophysical properties ( p -wave velocity, gamma-ray density, acoustic impedance, magnetic susceptibility and porosity), Si, total organic carbon and calcium carbonate were considered. The data revealed three main periods of sediment accumulation: (i) from 10.8 cal kyr BP to 7.6 cal kyr BP the sediment was coarse, Si content was high (27%), the magnetic susceptibility was low and the presence of shell fragments all suggest a period of low continental input and the deposition site was shallow (i.e, lower sea level); (ii) from 7.5 cal kyr BP to 4.6 cal kyr BP the elevated ratios of Al/Ca (0.69 ± 0.08), Fe/Ca (0.27 ± 0.04), Sr/Al (31.57 ± 4.47) ×10 −4, Cd/Al (0.09 ± 0.03) ×10 −5 and Ba/Al (0.70 ± 0.16) ×10 −4 are consistent with a period of maximum sea transgression and elevated influence of the nutrient-rich South Atlantic Central Water (SACW); (iii) from 4.5 cal kyr BP to the present, events of higher fluxes of TOC, Ni, Cu and Zn were observed from ca 3.2 cal kyr BP to 3.4 cal kyr BP, in both cores, related to humid climate. Overall, the multi-proxy approach shed light on the effects of climate and oceanographic variability on sediment input and accumulation in a less-studied portion of the Brazilian shelf, which are consistent with other shelf areas and with changes in regional climate systems like the Intertropical Convergence Zone (ITCZ), South American Monsoon Systems (SAMS) and South Atlantic Convergence Zone (SACZ).